TRANSLATION QUALITY ASSESSMENT AT THE CROSSROADS OF ETHNOLINGUISTICS AND ETHNOGRAPHY: TARAS SHEVCHENKO’S “IRZHAVETS” IN ENGLISH TRANSLATIONS - Shmiher, Taras (Vertimo studijos, 2017)
Ethnographic approaches to understanding a text and its cultural values have been scarcely developed from the viewpoint of linguistic verification in translation criticism. Methods of studying cultural material which focus on the environment and behaviour can be borrowed from Ethnography for identifying and assessing cultural values in the texts of an original and a translation. The case study is performed on the key personality in Ukrainian cultural history, the poet, artist and thinker Taras Shevchenko (1814–1861) whose poetic texts turned out to be prophetical for constructing the Ukrainian political nation out of ethnic mass and building the future Ukrainian nation-state. ‘Translation is museum’ is no longer an eloquent metaphor, but a multi-layered concept in the system of text typology. The starting point for the ethnographic analysis of the original-translation relations is collective memory as a textual category. Close to intertextuality which is oriented toward a variety of existing and connected texts, collective memory enables one to focus on the selectiveness of cultural information as actualized – really or probably – in a newly generated text. Axiological values in the text should be interpreted via the symbolization of an event. This symbolization along with cultural compatibility, implications and misunderstandings offer a close set of criteria for textual comparisons. The finalized ethnographic system of contrasting an original and a translation contribute to the cultural interpretation of a text, so needed in translation criticism.